ROLE OF COAL-DERIVED HUMIC ACID IN THE AVAILABILITY OF NUTREINTS AND GROWTH OF SUNFLOWER UNDER CALCAREOUS SOIL - S. A. Sadiq; D. M. Baloch; N. Ahmed; Hidayatullah (Journal of Animal and Plant Sciences, 2014)
The soils of Pakistan are calcareous alkaline and poor in organic matter where the availability of nutrients is limited resulting in low crop yield per hectare. However, there are enriched deposits of low rank coal containing humic acid (HA) in large quantities which can be used as a source of organic matter. Taking advantage of this natural resource, the present study was designed to evaluate the different concentration of coal-derived HA (0, 0.5, 1, 1.5, 5 and 25 g l-1)  on growth of sunflower in pot experiments arranged in a completely randomized design with a basal dose of NPK and replicated four times. The results indicated that shoot (58.84 g) and root dry weight (18.24 g), soil organic matter and leaf nutrient concentration except Cu and Mn of sunflower improved significantly when humic acid was applied up to 1g l-1 while further increase in HA resulted suppressive effects on all studied parameters. However, soil pH decreased significantly with increasing HA that enhanced nutrient availability. It was concluded that the application of coal-derived HA with low concentration under calcareous soil can help in improving soil quality and increasing yield on sustainable basis.
Keywords: Coal-derived humic acid; nutrients; growth; sunflower; calcareous soil